Joy-bearing grief : tears of contrition in the writings of the early Syrian and Byzantine fathers - Hunt, Hannah (Medieval Mediterranean ;, 2004)
"This volume is the first full-length study of penthos (tears of contrition) since Hausherr's in 1944. It traces its exposition in the early eastern Christian tradition, through detailed analysis of Greek and Syriac texts by Klimakos, Ephrem, Isaac and Symeon the New Theologian. It suggests why such weeping is, for these writers, a joyful as well as a sobering experience, and it places their writings in their historical and geographical context, giving some lexicographical background. Issues of religious anthropology, and the unusual choice of a female exegete in the person of the 'sinful woman' (Luke 7.36-50) are considered. The conclusion points the way to an appropriate theological interpretation of these teachings and highlights modern, non-monastic examples of joy-bearing, penitent grief."--Jacket